2017
DOI: 10.1039/c7nr02376f
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-selective electrokinetic enrichment of biomolecules in physiological media based on electrical double-layer polarization

Abstract: Proteomic biomarkers of interest to the early diagnosis of diseases and infections are present at trace levels versus interfering species. Hence, their selective enrichment is needed within bio-assays for speeding binding kinetics with receptors and for reducing signal interferences. While DC fields can separate biomolecules based on their electrokinetic mobilities, they are unable to selectively enrich biomarkers versus interfering species, which may possess like-charges. We present the utilization of AC elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…Lower frequencies (100–300 kHz) produced pDEP while higher frequencies (1 MHz) produced nDEP . More recent study by these groups reported the use of nanoslit devices for the ultrafast enrichment of biomarkers and label‐free quantification of intracellular mitochondrial modifications . These recent reports further demonstrate the great applicability of iDEP for trapping, enrichment, and manipulating of relevant nanobioparticles of interest.…”
Section: Advances On Devices For Trapping Idepmentioning
confidence: 87%
See 1 more Smart Citation
“…Lower frequencies (100–300 kHz) produced pDEP while higher frequencies (1 MHz) produced nDEP . More recent study by these groups reported the use of nanoslit devices for the ultrafast enrichment of biomarkers and label‐free quantification of intracellular mitochondrial modifications . These recent reports further demonstrate the great applicability of iDEP for trapping, enrichment, and manipulating of relevant nanobioparticles of interest.…”
Section: Advances On Devices For Trapping Idepmentioning
confidence: 87%
“…Figure D shows nDEP trapping of 200 nm red particles with “low” surface charge, these particles are pushed out of the constriction region by nDEP. Successful trapping of nanoparticles has also been demonstrated in devices with nano‐constrictions, the Swami research group and the Chou research group have worked substantially on this area, some of their findings have been published in collaboration . In 2012 they demonstrated pDEP and nDEP of streptavidin proteins employing a device with nano‐constrictions.…”
Section: Advances On Devices For Trapping Idepmentioning
confidence: 99%
“…In addition to artificial sub‐micron nanoparticles, DEP has recently been applied to smaller biological nano‐objects: proteins, nucleic acids, and extracellular vesicles . In the case of proteins and nucleic acids, the required very high electric field gradients are achieved using sub‐micron and nanometer‐scale electrode gaps, that concentrate the electric field gradients in extremely small volumes.…”
Section: Introductionmentioning
confidence: 99%
“…[27] DEP is of interest for the development of lab-on-chip analysis methods, [28] and has been used to concentrate plasmonic particles for various modes of Raman spectroscopy. [27,29] In addition to artificial sub-micron nanoparticles, DEP has recently been applied to smaller biological nano-objects: proteins, [30][31][32][33][34] nucleic acids, [35,36] and extracellular vesicles. [37,38] In the case of proteins and nucleic acids, the required very high electric field gradients are achieved using sub-micron and nanometer-scale electrode gaps, that concentrate the electric field gradients in extremely small volumes.…”
Section: Introductionmentioning
confidence: 99%
“…With nDEP enrichment inside the nanoslit device, no significant difference is observed between the immunoassay with just 50 pg/mL PSA versus that with an additional level (210 4 -fold higher levels) of interfering antimouse IgG antibodies. The kinetic plot in Figure 11b shows that steady-state signals can be reached within 2 minutes of binding under nDEP enrichment of PSA, whereas in the absence of nDEP enrichment the signal does not reach a steady-state level, presumably due to anti-mouse IgG induced non-specific binding that causes false positives [68].…”
Section: E Eliminating False-positives On Psa Immunoassaymentioning
confidence: 99%